Proliferative Tumor Doubling Times of Prostatic Carcinoma - Priya N. Werahera; L. Michael Glode; Francisco G. La Rosa; M. Scott Lucia; E. David Crawford; Kenneth Easterday; Holly T. Sullivan; Rameshwar S. Sidhu; Elizabeth Genova; Tammy Hedlund (Prostate Cancer, 2011)
Prostate cancer (PCa) has a variable biology ranging from latent cancer to extremely aggressive tumors. Proliferative activities of cancers may indicate their biological potential. A flow cytometric assay to calculate maximum proliferative doubling times (Tmax) of PCa in radical prostatectomy specimens after preoperative in vivo bromodeoxyuridine (BrdU) infusion is presented. Only 4/17 specimens had tumors large enough for flow cytometric analysis. The Tmax of tumors was similar and ranged from 0.6 to 3.6 months. Tumors had calculated doubling times 2- to 25-fold faster than their matched normal tissue. Variations in labeling index and Tmax were observed within a tumor as well as between different Gleason grades. The observed PSA doubling times (PSA-DT) ranged from 18.4 to 32.0 months, considerably slower than the corresponding Tmax of tumors involved. While lack of data for apoptotic rates is a limitation, apparent biological differences between latent versus aggressive PCa may be attributable to variations in apoptotic rates of these tumors rather than their cell proliferative rates.